Traces of the Foreign The Reception of Translations of Spanish American Prose in Poland in 1945-2005 from the Perspective of Intercultural Communication - Gaszyńska-Magiera, Małgorzata (Studies in Language, Culture and Society, 2019)
The aim of this monograph is to present the traces of intercultural encounters between Poland and Latin America realized by means of literary translations produced in the post-war period. It considers various aspects of the reception of Polish translations of Spanish American prose in 1945-2005 by examining their presence on the book market in the communist times and after 1990 in free market conditions. The analyses of critical texts show the attitudes of Polish critics towards this prose over the years. Survey research presents motives, behaviours and needs developed in different epochs by Polish readers. The interdisciplinary character of the monograph involves methodology inspired by translation, reception and cultural studies, sociology of literature and intercultural semantics.